What do journals' author instructions state on search methods for systematic reviews: from evidence to implementation (Journal of EAHIL, 2025)
Systematic reviews are essential in clinical decision-making, policy development, and evidence-based practice. Our previous research identified significant gaps in author instructions of biomedical and health journals regarding search methods for systematic reviews. To address this, we engaged with key stakeholders to disseminate our research findings and provide recommendations to implement and improve the quality of journals’ author instructions, ultimately contributing to enhancing the quality of published systematic reviews. This brief note outlines the strategy and outcomes of this implementation project. Despite our efforts, limited adoption of our recommendations appears to be primarily due to misconceptions about relevance to different journal scopes, competing editorial priorities, resource constraints related to time and expertise needed for implementation, and a lack of clear responsibility or accountability. Further outreach is needed to raise awareness and improve the quality of  journals’ author instructions.